KEGIATAN EKSTRAKURIKULER TERHADAP HASIL BELAJAR AKUNTANSI SISWA KELAS XI AKUNTANSI DI SMK - Kiki Yanti; Warneri Warneri; Okiana Okiana (Universitas Tanjungpura, 2021)
AbstractThe aims of this study are to determine (1) How are extracurricular activities at SMKMandiri Pontianak (2) How are the results of learning Accounting of XI studentsAccounting class at SMK Mandiri Pontianak (3) Is there an effect of extracurricularactivities on learning outcomes of Accounting in XI students Accounting class at SMKMandiri Pontianak. Using the quantitative descriptive method with the form ofrelationship studies, the data source for the XI grade students of accounting at SMKMandiri Pontianak. Data collection techniques: Questionnaires and Documentaries.Prerequisite test: validity and reliability test. Data processing techniques: Simple LinearRegression. The t value of 0.035 compared to the t table with a significance level of 0.05of 0.254 means that t is smaller than the t table of 0.035 <0.254 so that Ha is acceptedand Ho is rejected. Simple linear regression calculation obtained Y '= 71.584 + 0.035 Xmeans that the regression coefficient is 71.584, meaning that every time you add 1% tothe variable (X), the value of the variable (Y) increases by 0.035. The result of theregression coefficient influence (X) on (Y) is 1.2%, the rest is influenced by other factorsnot explained in this study. In conclusion, extracurricular activities do not have asignificant effect on learning outcomes of accounting students in XI accounting classstudents at SMK Mandiri Pontianak.Keywords : Extracurricular Activities, Accounting Learning Outcomes